Synthesis of α-MoO3 nanoplates using organic aliphatic acids and investigation of sunlight enhanced photodegradation of organic dyes. (April 2016) - Kumar, V. Vinod; Gayathri, K.; Anthony, Savarimuthu Philip
Graphical abstract: Thermodynamically stable α-MoO3 nanoplates and nanorods were synthesized using organic structure controlling agents and demonstrated sun light enhanced photocatalytic degradation of methylene blue (MB) and rhodamine blue (Rh-B) dyes in aqueous solution. Highlights: α-MoO3 hexagonal nanoplates using organic structure controlling agents. Tunable optical band gap of MoO3 . Demonstrated strong sun light mediated enhanced photodegradation of methylene blue and rhodamine blue. Photodegradation did not use any other external oxidizing agents. Abstract: Thermodynamically stable α-MoO3 nanoplates were synthesized using organic aliphatic acids as structure controlling agents and investigated photocatalytic degradation of methylene blue (MB) and rhodamine blue (Rh-B) in presence of sun light. Three different organic aliphatic acids, citric acid (CA), tartaric acid (TA) and ethylene diamine tetra-acetic acid (EDTA), were employed to control morphologies. CA and TA predominantly produced extended hexagonal plates where EDTA gave nanorods as well as nanoplates. PXRD studies confirmed the formation of α-MoO3 nanoparticles. HR-TEM and FE-SEM reveal the formation of plate morphologies with 20–40 nm thickness, 50–100 nm diameter and 600 nm lengths. The different morphologies of α-MoO3 nanoparticles lead to the tunable optical band gap between 2.80 and 2.98 eV which was obtained from diffused reflectance spectra (DRS). Interestingly, the synthesized α-MoO3 nanoplates exhibited strong photocatalytic degradation of MB and Rh-B up to 99% in presence of sun light without using any oxidizing agents.